Microcontroller theory and applications with the PIC18F - Rafiquzzaman, Mohamed (Hoboken, New Jersey : John Wiley & Son, Inc., 2011)
Microcontrollers play an important role in the design of digital systems. They are found in a wide range of applications including office automation systems (copiers and fax machines), consumer electronics (microwave ovens), digital instruments, and robotics.
1. Introduction to Microcontrollers -- 2. Microcontroller Basics -- Introduction to Programming Languages -- Microcontroller Memory and Input/Output (I/O) -- PIC18F Architecture and Addressing Modes -- Assembly Language Programming with the PIC18F: Part 1 -- Assembly Language Programming with the PIC18F: Part 2 -- PIC18F Hardware and Interfacing: Part 1 -- PIC18F Hardware and Interfacing: Part 2 -- Basics of Programming the PIC18F Using C.
Includes bibliographical references and index.
Keywords: MICROCONTROLLERS